2016
DOI: 10.1177/0033294116682945
|View full text |Cite
|
Sign up to set email alerts
|

Are Sex Effects on Ethical Decision-Making Fake or Real? A Meta-Analysis on the Contaminating Role of Social Desirability Response Bias

Abstract: A meta-analysis of 143 studies was conducted to explore how the social desirability response bias may influence sex effects on ratings on measures of ethical decision-making. Women rated themselves as more ethical than did men; however, this sex effect on ethical decision-making was no longer significant when social desirability response bias was controlled. The indirect questioning approach was compared with the direct measurement approach for effectiveness in controlling social desirability response bias. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 72 publications
0
19
0
1
Order By: Relevance
“…Similarly, women also underreported bile consumption, reflecting findings of sensitivities around bile use among women in Vietnam . This could be linked to findings that women tend to answer direct questions in ways that make them appear more ethical than they are, due to being broadly more affected by social desirability biases than men (Yang et al, 2017). This may include over-stating how much they consider animal welfare issues when making purchasing decisions (Lusk & Norwood, 2010), although differences in focus on animal welfare between male and female consumers have not been observed in Chinese studies on the meat industry (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, women also underreported bile consumption, reflecting findings of sensitivities around bile use among women in Vietnam . This could be linked to findings that women tend to answer direct questions in ways that make them appear more ethical than they are, due to being broadly more affected by social desirability biases than men (Yang et al, 2017). This may include over-stating how much they consider animal welfare issues when making purchasing decisions (Lusk & Norwood, 2010), although differences in focus on animal welfare between male and female consumers have not been observed in Chinese studies on the meat industry (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we dropped these three items and only used the remaining 14 items to measure subordinates' deviant behavior. As admitting doing deviant behavior posted a threaten to the self-image of subordinates, the measuring of deviant behavior was found to be sensitive to the social desirability response bias (Yang et al, 2017). Moreover, we collected data in a call center where employees were working in the same small space with their supervisor and colleagues, and employees were also closely monitored by their supervisors.…”
Section: Deviant Behaviormentioning
confidence: 99%
“…Therefore, we believed it was necessary to take precautionary measures of mitigating the social desirability tendency of respondents. Accumulative evidence in behavioral ethics literatures had indicated that the indirect questioning method could help reduce the social desirability response bias in measuring construct prone to social influences (Fisher, 1993), the measurement of deviant behavior as an example (Yang et al, 2017). We employed this technique in the current study to reduce the social desirability bias in measuring subordinates' deviant behavior.…”
Section: Deviant Behaviormentioning
confidence: 99%
“…Predominantly, male groups also tended to make greater advances. This may be due to a greater average maturity of women in terms of moral sensitivity, for instance (You et al, 2011), or a lower tendency of men to identify themselves as moral/ethical (Yang et al, 2017). Both factors might lead to women learning "less" because they cannot achieve the same pre-/post-differences that men do.…”
Section: Discussionmentioning
confidence: 99%